Studies on the Fischer-Tropsch synthesis over RuCo/SiC-Al2O3 structured catalyst - Noh, Young Su; Lee, Kwan-Young; Moon, Dong Ju (ELSEVIER, 2020)
RuCo/SiC-Al2O3 catalysts were with enhancing thermal conductivity for the Fischer-Tropsch Synthesis (FTS) were designed and manufactured. The SiC-Al2O3 support was extruded by Lab scale extruder and then foamed by the marumerizer. Catalysts were prepared by an incipient wetness impregnation method. All the prepared catalysts were characterized by SEM-EDX, XRD, TPR, TPD, XPS, ICP and N-2-physisorption techniques. The catalytic performance was evaluated at T = 210-230 degrees C, P = 20 bar and GHSV of 1,000 h(-1) in a fixed bed reactor system. The CO conversion over RuCo/nSiC-Al2O3 catalysts was increased by 10% compared to RuCo/Al2O3 catalyst at 210 degrees C. Furthermore, the selectivity of methane was similar or less than RuCo/Al2O3 catalyst. It was shown that the CO conversion increased with increasing the SiC content from 5 to 15 wt%, and then decreased. The RuCo/15SiC-Al2O3 catalyst showed higher CO conversion than other catalysts under the tested conditions. This is because the 15 wt.% SiC addition ratio is the most advantageous between thermal conductivity improvement and aggregation of cobalt particles.
Keywords: THERMAL-CONDUCTIVITY; COBALT; DISPERSION